Analisis Faktor-faktor yang Mempengaruhi Penerimaan dan Penggunaan Mobile Payment pada Teknologi Pembayaran Gopay - Wilbert Sinclair; Lailan Maulia; Tina Novianti Sitang (Politeknik Ganesha Medan, 2021)
This study aims to determine the factors that influence the acceptance and the use of mobile payments in GOPAY payment technology by integrating the Technology Acceptance Model (TAM) theory, mobile payment characteristics, trust and security, and privacy. The research method used is a survey method. The sample of this research is GOPAY users in the Faculty of Economics at Prima Indonesia University, with as many as 222 (two hundred and twenty-two) respondents through an online questionnaire. Data analysis using Smart Partial Least Square (PLS) 3.0. The results of this study can be concluded that the factors that influence the acceptance and the use of mobile payments on GOPAY payment technology are mobile payment characteristics, trust and security, and privacy which is not supported in this study. GOPAY has the characteristics of mobility, reachability, compatibility, and convenience. The characteristics of mobile payments are not supported because users cannot experience the benefits. Trust is not supported because not all users trust GOPAY, especially in the process of topping up balances and receiving cashback after making payment transactions. Security and privacy are not supported because users do not trust GOPAY regarding topping up balances, if the balance does not come in, they can contact the bank.